Tensile and impact properties of hybrid composites from textile waste / Amir Hafizin Mohamad Azminor, Nurul Syafiqah Zabidi and Bibi Intan Suraya Murat - Mohamad Azminor, Amir Hafizin; Zabidi, Nurul Syafiqah; Murat, Bibi Intan Suraya (UiTM Press for the Research Management Center (IRMI), Universiti Teknologi MARA, 2021)
The rise of the textile industry in global fashion has caused a high level of post-consumer textile waste generation. Every year, million tons of textile waste has been sent to landfills that consequently leading to environmental pollution. This study aimed to use the textile waste for the development of hybrid composite laminate, together with the existing commercially available fibreglass. This research investigated the tensile properties and impact strength of textile waste hybrid composites. Three textile variants were used in this study, which is lycra, polyester and cotton, and they were either chopped or used as a full fabric. Hand lay-up and hot press technique were used to produce the sample materials, using epoxy resin as the binder. A total of 9 samples were prepared and their tensile and impact properties were assessed. Tensile test results showed that all hybrid composites have a better ultimate tensile strength and tensile modulus compared to their original raw fabrics, but not on the elongation property. It can be seen that the arrangement of fabrics has a distinctive eJect on tensile and impact strength. All raw fabrics were greatly punctured during the failure, but all hybrid composites have barely visible impact damage on the front surface, and no penetration was observed. This study reveals that the reuse of textile waste and fibreglass for the development of hybrid composites has a huge potential to be used as substitutes in other composite materials. In the future, this will contribute to improving the sustainability of textile materials.